New page design : layout & editorial design 2026-02-15T18:09:03+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Wang, Shaoqiang (Hoaki Books, S.L., 2022)

(untitled)
"Now in paperback, New Page Design offers a comprehensive technical explanation of basic layout principles, a crucial graphic design field that covers the arrangement of typefaces, images, colours, objects, and grids on a page. New Page Design presents also a panorama of contemporary editorial design trends and styles through a selection of 100 projects, from newspapers and magazines to catalogues, books, brochures and posters. Supported by case studies and tips and tricks, within this book readers will gain an overall understanding of the fundamentals of editorial design, including paper size, typographic units, the history of typography and the styles of different typefaces, layout elements, interaction between sections, and the optimum way to visually convey a message. It is a perfect reference for designers who are looking for practical solutions and inspiration. The book includes interviews with Bruch --Idee & Form, Any Studio, Pyramid and Linus Lohoff"--